The Validation of Antibodies Suitable for Flow Cytometric Analysis and Immunopeptidomics of Peptide–MHC Complexes in the Outbred Swiss Albino Mouse Strain - Shanzou Chung; Isambard G. Knox-Johnson; Sarah E. Gazzard; Runqiu Song; Ngoc H. Le; Luise A. Cullen-McEwen; John F. Bertram; Anthony W. Purcell; Asolina Braun (Methods and Protocols)
Antigen presentation on major histocompatibility complex (MHC) molecules is central to the initiation of immune responses, and a lot of our understanding about the antigen processing and presentation pathway has been gained through studies in mice. MHC molecules are the most genetically diverse genes; consequently, mouse strains differ substantially in their MHC make up and resulting antigen presentation. Swiss mice are commonly used in pharmacological research, yet our understanding of antigen presentation in this strain is surprisingly limited. Here, we have tested a range of anti-MHC antibodies and present a range of clones suitable to analyse MHC class I and class II molecules in Swiss mice who have the H2-q MHC haplotype. Moreover, we demonstrate using immunopeptidomics that clones 28-12-8, 34-1-2, MKD6, and N22 are also suited to isolate MHC class I and class II ligands in this mouse strain. Thus, this work also establishes a first experimental account of the H2-q-derived thymus and spleen immunopeptidome in Swiss mice which bears strong resemblance with ligands isolated from the H2-d MHC haplotype of Balb/C mice. The analysis of source proteins shows common but also organ- and function-specific antigen presentation in line with the involvement of the thymus in tolerance induction and the function of the spleen as a site of immune responses.